2015
DOI: 10.1016/j.jhep.2015.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Essential roles of FoxM1 in Ras-induced liver cancer progression and in cancer cells with stem cell features

Abstract: Background & Aims Over-expression of FoxM1 correlates with poor prognosis in hepatocellular carcinoma (HCC). Moreover, the Ras-signaling pathway is found to be ubiquitously activated in HCC through epigenetic silencing of the Ras-regulators. We investigated the roles of FoxM1 in Ras-driven HCC, and on HCC cells with stem-like features. Methods We employed a transgenic mouse model that expresses the oncogenic Ras in the liver. That strain was crossed with a strain that harbor floxed alleles of FoxM1 and the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
85
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 32 publications
(52 reference statements)
4
85
0
Order By: Relevance
“…Its over-expression coincides with high-grade progression in almost all types of cancers, including those in breast12, liver34, lung56, prostate78, pancreas910, ovary11, brain12, nasopharynx13, esophagus14, and also in certain leukemia15. Moreover, a study that analyzed 18,000 human tumors with outcomes for 39 different malignancies identified over-expression of FoxM1 as a major predictor for poor prognosis16.…”
mentioning
confidence: 99%
“…Its over-expression coincides with high-grade progression in almost all types of cancers, including those in breast12, liver34, lung56, prostate78, pancreas910, ovary11, brain12, nasopharynx13, esophagus14, and also in certain leukemia15. Moreover, a study that analyzed 18,000 human tumors with outcomes for 39 different malignancies identified over-expression of FoxM1 as a major predictor for poor prognosis16.…”
mentioning
confidence: 99%
“…Secondly, FoxM1 is not expressed, or is expressed at very low levels in normal tissues [21]. Thirdly, FoxM1 plays an essential role in HCC cell migration, invasion, as well as liver cancer progression and in cancer cells with stem cell features [15, 22]. Fourthly, clinicopathologic studies suggest that FoxM1 expression correlated with poorly-differentiated HCC tumors with intrahepatic metastasis, which is a leading cause of post-surgical recurrence and low survival rate [20, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that FoxM1 was essential for development of HCC, and overexpression of FoxM1 was associated with aggressive tumor features and poor prognosis [20]. In fact, FoxM1 could induce an epithelial-mesenchymal-like transition phenotype in HCC cells, increase cell migration, and induce premetastatic niche at the distal organ of metastasis [21, 22]. Down-regulation of FoxM1 could suppress the proliferation of HCC cells and inhibit HCC growth [23].…”
Section: Introductionmentioning
confidence: 99%
“…Further encouraged by new evidence indicating that FOXM1 (1) drives tumor development and progression 1519 by virtue of a complex mechanism that includes enhanced cell proliferation, migration and invasion 6 , regulation of the DNA damage response 20 and changes in the cancer epigenome 21 , (2) promotes cancer-cell resistance to ionizing radiation 22 and cytotoxic drugs 23 , (3) governs, in part, the survival and tissue-regenerating capacity of both normal hematopoietic stem cells 24 and malignant stem cell-like cells 25 , (4) links acquired resistance to cancer therapy with cancer stemness 26 and (5) owing to the development of specific small-molecule inhibitors 27 , may soon be targeted more effectively than possible in the past 28 , we here decided to evaluate whether FOXM1 might play an important but heretofore overlooked role in plasma cell myeloma.…”
Section: Introductionmentioning
confidence: 99%